2023
DOI: 10.1097/01.hjh.0000913356.83879.cf
|View full text |Cite
|
Sign up to set email alerts
|

S-28-3: Comparative Effectiveness and Implementation of Digital Health Interventions for People With Hypertension: Systematic Review and Meta-Analysis of Randomised Controlled Trials

Abstract: Background:Digital health interventions are effective for hypertension self-management, but a comparison of the effectiveness and implementation of the different modes is lacking. This study aimed to compare the effectiveness of short message service (SMS), smartphone application and website interventions on improving blood pressure in people with hypertension, and to report on their reach, uptake and feasibility.Methods:CINAHL, Cochrane Central, Embase, Medline and PsychInfo were searched on 25th May 2022 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In contrast, a study by Siopis et al., 16 comparing the efficacy of SMS, smartphone app, and website interventions on improving BP in adult patients with hypertension found that smartphone app and website interventions provided a greater remarkable reduction in SBP and DBP compared with SMS interventions. The disparities between these studies are that our study was centred on LMICs, whereby more people cannot afford smartphones with applications, compared with the study by Siopis et al., 16 which assessed digital health interventions globally. Second, due to challenges in accessing internet services, more people in LMICs own a telephone with SMS capacity compared to smartphones.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…In contrast, a study by Siopis et al., 16 comparing the efficacy of SMS, smartphone app, and website interventions on improving BP in adult patients with hypertension found that smartphone app and website interventions provided a greater remarkable reduction in SBP and DBP compared with SMS interventions. The disparities between these studies are that our study was centred on LMICs, whereby more people cannot afford smartphones with applications, compared with the study by Siopis et al., 16 which assessed digital health interventions globally. Second, due to challenges in accessing internet services, more people in LMICs own a telephone with SMS capacity compared to smartphones.…”
Section: Discussionmentioning
confidence: 87%
“… 52 Similarly, a study with global individual data (n = 7092 respondents) confirmed that digital health intervention provides a notable reduction in SBP by 3.62 and DBP by 2.45 mm Hg compared with the control. 16 The similarity across the studies could be attributed to the inclusion of some respondents on antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations